Triplet Male Lambs Are More Susceptible than Twins to Dietary Soybean Oil–Induced Fatty Liver. Issue 6 (9th May 2019) - Wang, Bo; Qu, Yanghua; Wang, Yiping; Ma, Yong; Xu, Chenchen; Li, Fadi; Liu, Ce; Lu, Xiaonan; Wang, Bo; Xiu, Peng; Gao, Yuefeng; Diao, Zhicheng; et al.
ABSTRACT: Background: Litter size affects fetal development but its relation to diet-induced fatty liver later in life is unknown. Objectives: This aim of this study was to test the hypothesis that litter size influences postweaning fatty liver development in response to soybean oil–supplemented diet. Methods: Weanling twin (TW) or triplet (TP) male lambs ( n = 16) were fed a control diet or 2% soybean oil–supplemented diet (SO) for 90 d. Liver tissue morphology, biochemical parameters, and lipid metabolic enzymes were determined. Hepatic gene expression was analyzed by RNA sequencing ( n = 3), followed by enrichment analysis according to Gene Ontology and the Kyoto Encyclopedia of Genes and Genomes. Differentially expressed genes involved in lipid metabolism were further verified by quantitative reverse transcriptase-polymerase chain reaction ( n = 4). All data were analyzed by a 2-factor ANOVA, apart from differentially expressed genes, which were identified by the Benjamini-Hochberg approach ( q value ≤0.05). Results: SO increased liver triglyceride (by 55%) and nonesterified fatty acid (by 54%) concentrations in TPs ( P ≤ 0.05) but not in TWs ( P > 0.05). SO also induced a 2.3- and 2.1-fold increase in the liver steatosis score of TPs and TWs, respectively ( P ≤ 0.05). Moreover, SO reduced the activity of lipolytic enzymes including hepatic lipase and total lipase in TPs by 47% and 25%, respectively ( P ≤ 0.05). In contrast, activities of lipogenic enzymes, including malic enzyme and acetyl coenzyme A carboxylase, were significantly higher in TPs ( P ≤ 0.05). Moreover, TPs had higher expression of lipogenic genes, such as FASN (by 45%) and APOB (by 72%), and lower expression of lipolytic genes, such as PRKAA2 (by 28%) and CPT1A (by 43%), compared with TWs ( P ≤ 0.05). Conclusions: TPs have a gene expression profile that is more susceptible to SO-induced fatty liver than that of TWs, which indicates that insufficient maternal nutrient supply at fetal and neonatal stages may increase the risk of nonalcoholic fatty liver disease.